2001
DOI: 10.1128/jcm.39.5.1859-1864.2001
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Serology: Importance of Methodology in Patients with Coronary Heart Disease and Healthy Individuals

Abstract: Most publications on the relationship between infection with Chlamydia pneumoniae and coronary heart disease (CHD) propose an association, but negative studies are also reported. Seroepidemiological studies vary in the use of different serological methods, different cutoff limits, different sampling times in relation to acute cardiac events, and different clinical stages of CHD. We wanted to compare three different commercially available methods for measuring Chlamydia antibodies to see how the choice of metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
(46 reference statements)
1
35
0
Order By: Relevance
“…All these samples also had IgG antibodies, and in total, 70% of the IgG-positive samples were IgA positive as well. Schumacher et al have also been reported a lower prevalence of IgA than of IgG in healthy controls (44). Therefore, detection of IgG seems to be the more sensitive method for determination of the seroprevalence of anti-C. pneumoniae antibodies in a healthy population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All these samples also had IgG antibodies, and in total, 70% of the IgG-positive samples were IgA positive as well. Schumacher et al have also been reported a lower prevalence of IgA than of IgG in healthy controls (44). Therefore, detection of IgG seems to be the more sensitive method for determination of the seroprevalence of anti-C. pneumoniae antibodies in a healthy population.…”
Section: Discussionmentioning
confidence: 98%
“…We found 30 (54%) of the truepositive samples to be positive by rELISA. In addition, it has been found that rELISA detects a lower prevalence of Chlamydia-specific IgG antibodies than MIF does in patients with chronic obstructive pulmonary disease and coronary heart disease (44,46). Most of the samples which were found to be positive by the rELISA had high antibody titers by MIF, which might indicate a very recent infection.…”
Section: Discussionmentioning
confidence: 99%
“…The MC rELISA was used for Chlamydia LPS analysis and therefore was not able to differentiate between antibodies against the different Chlamydia species, e.g., C. pneumoniae, C. trachomatis, and C. psittaci. However, discordant serological results between MIF and the MC rELISA should not necessarily be ascribed to the Chlamydia species specificity versus the genus specificity of the tests, since differences could also exist in the human immunological response, as suggested by Schumacher et al (25). In addition, cross-reactions between the different chlamydial species have recently been reported with the MIF test, bringing into question the specificity of the reference test.…”
Section: Vol 41 2003mentioning
confidence: 95%
“…In contrast to MIF tests, enzyme immunoassays are easier to perform, less time-consuming, and more objective because of the photometric reading involved. Nevertheless, three recent studies have demonstrated that the link between C. pneumoniae and coronary artery disease depends on the serologic method chosen to measure the C. pneumoniae antibodies (29,45,62).In summary, although initial reports were positive, the later ones, often prospectively designed and adjusted for known cardiovascular risk factors, showed a negative or weak positive association overall between seropositivity for C. pneumoniae and atherosclerosis. Importantly, methodology has a strong impact on the link between C. pneumoniae and atherosclerosis.…”
mentioning
confidence: 96%
“…In contrast to MIF tests, enzyme immunoassays are easier to perform, less time-consuming, and more objective because of the photometric reading involved. Nevertheless, three recent studies have demonstrated that the link between C. pneumoniae and coronary artery disease depends on the serologic method chosen to measure the C. pneumoniae antibodies (29,45,62).…”
Section: Seroepidemiologic Studiesmentioning
confidence: 99%